Characterization of Aiphanes aculeata fruit pulp and application in ice cream formulations - Fernandes, Isabela de Andrade Arruda (2021)
The characteristic color of the palm fruits Aiphanes aculeata, also known as Cariota-de-Espinho, suggests the presence of pigments such as carotenoids and anthocyanins, in addition these fruits present other compounds with health benefits such as minerals, vitamins and phenolics. However, there are no studies on the application of these fruits in food formulations since this palm tree is used only for urban landscaping. The present study aimed to characterize the Aiphanes aculeata pulp for proximate composition, physicochemical parameters, mineral contents, bioactive compounds, and antioxidant activity. Three ice cream formulations with the addition of different pulp concentrations were also produced, aimed to contribute to the technological and nutritional use of Aiphanes aculeata fruits. The choice of ice cream as the main investigation occurs due to the importance of functional ice creams to the balance of the physiological functions of the human organism that occurs through the ingestion of active and nutritional ingredients. Ice creams were characterized for overrun, melting behavior, color, and texture profile. The pulp presented representative minerals levels such as iron (49.82 ± 43.85 mg/100g) and zinc (96.07 ± 81.65 mg/100g). The total carotenoids level was significant, corresponding to 92.64 ± 0.83 μg/100g, with an emphasis on the beta-carotene levels (56.94 ± 2.11 μg/100g). The different pulp concentrations used in the formulations influenced the characteristics of the ice cream, as it interacted positively with the ingredients until the concentration of 30% pulp. Therefore, the Aiphanes aculeata fruits showed potential for application in the food industry, in the manufacture of ice cream with high nutritional value.